Deteksi Perkembangan Anak Usia 3 Bulan – 72 Bulan Menggunakan Kuesioner Pra Skrining Perkembangan (KPSP) - Entoh, Christina; Noya, Fransisca; Ramadhan, Kadar (Poltekita: Jurnal Pengabdian Masyarakat, 2020)
More than a third of children in the world experience growth and development disorders both physically and mentally, and an estimated 5 to 10% of the child population has developmental delays. Child development problems such as motor delays, language, behavior, autism, hyperactivity, have increased in recent years, the occurrence in the United States ranges from 12-16.6%, Thailand 24%, Argentina 22.5%, and in Indonesia between 13 % -18%. Approximately 16% of children under five years old (toddlers). Indonesia experiences neurological and brain development disorders ranging from mild to severe. The purpose of this study is to increase the motivation of toddlers to carry out routine child development checks, increase the participation of toddlers to carry out child development checks using KPSP, early detection of growth, and developmental disorders. The method used in this community service is varied lectures. The speakers did a demonstration to mothers who have children of 3 - 72 months. Each mother gave information about their child's age and early detection of growth and development using KPSP according to the age child age. Results: Out of 140 children aged 3 - 72 months who were detected developmentally using the Pre Development Screening Questionnaire (KPSP), there were 134 children (95.7%) with normal results and 6 people (4.3%) with doubtful results and none (0%) who experienced deviance. Conclusion: The 6 children with doubtful screening results, after 2 weeks of screening, obtained 100% normal developmental results. Suggestion: Early detection can find growth disorders and child development, therefore, an intervention can be done as early as possible.